Sosialisasi Berorganisasi dengan Mengadopsi Gaya Kepemimpinan Melayani (Servant Leadership) - Grace Maria Fitricia; Faizal Rizky Yuttama; Iin Dyah Indrawati (Pusat Riset dan Inovasi Nasional, 2024)
Abstract. People in organization surely will face the dynamics of relationship between the member of oragnizations and need a good interpersonal and good communication between each member to work together, make a teamwork for running the work programs in each of team or division existing in organization. Good communication built can’t be separated from the leadership style of the leaders in organization. The leaders have to apply the effective leadership approach to communicate the vision and mission which will be achieved by organization, delegating task, teamwork with members and empower the organizational members. Servant leadership style is a leadership approach that fit to be applied in organization. The purpose to held this socialization is to invest the servant leadership style in college students in managing organizations and later for the long term purpose is to be practiced when entering the business work or entrepreneurship world.